Post‐glacial range revolutions in South European hares (Lepus spp.): Insights from ancient DNA and ecological niche modelling. (12th October 2018) - Lado, Sara; Farelo, Liliana; Forest, Vianney; Acevedo, Pelayo; Dalén, Love; Melo‐Ferreira, José
Abstract: Aim: The distribution of hares ( Lepus spp.) in southern Europe was markedly different at the Last Glacial Maximum. Historical hybridization during range replacements led to high frequencies of mtDNA introgression from Lepus timidus into populations of three other species in northern Iberian Peninsula, even though L. timidus subsequently disappeared from the region. We use palaeontological records to provide new insights on the biogeographic history of these range replacements, combining ancient DNA and ecological niche modelling. Location: Southern France. Taxon: Hares (genus Lepus ). Methods: DNA was extracted from hare bones collected at Neolithic sites in southern France (5.5–7.5 thousand years before present; kyrbp ) with uncertain species assignment. One mtDNA fragment was sequenced and 27 SNPs from 11 nuclear genes with species‐diagnostic information were genotyped. Distributions of L. granatensis, L. europaeus, and L. timidus were modelled using spatial and bioclimatic predictors, and the favourability function. Each model was transferred to 6 kyrbp and favourabilities were combined to determine the species with the highest environmental favourability in each sampled locality. Results: Ancient DNA analysis showed that the screened specimens belong to L. granatensis, a species presently confined to the Iberian Peninsula, but carried mtDNA haplotypes from L. timidus . Niche models show that L. granatensis achieved highest favourability in southern France 6 kyrbp reinforcing the molecular evidences. Main conclusions: L. granatensis replaced L. timidus populations from Iberia to southern France, being present in this region 5.5 kyrbp . Subsequent westwards invasion of L. europaeus likely replaced these L. granatensis populations towards northern Iberia, establishing current ranges. Despite successive species replacements, introgressed mtDNA haplotypes from L. timidus mark the distribution of the species in northern Iberian Peninsula before it disappeared in the region. Characterizing complex biogeographic histories of interacting species is a key to understand processes that led to current distributions of genetic diversity.